Social Presence Dan Sense Of Community Pada Anggota Komunitas Seni - Rachmawati; Audhrie Fernanda (Psychology Journal of Mental Health, 2019)
Abstrak. Penelitian ini bertujuan untuk mengetahui hubungan antara social presence dengan sense of community pada anggota komunitas seni Universitas Sriwijaya. Hipotesis penelitian ini ialah social presence memiliki hubungan dengan sense of community pada anggota komunitas seni Universitas Sriwijaya. Sampel penelitian sebanyak 100 orang. Teknik sampling menggunakan sampling kuota. Kuota sampel penelitian UKM Harmoni sebanyak 70 orang dan Komunitas X sebanyak 30 orang serta kuota sampel uji coba untuk UKM Harmoni adalah sebanyak 20 orang dan Komunitas X sebanyak 10 orang. Alat ukur yang digunakan adalah skala social presence dan sense of community yang mengacu pada dimensi social presence dari Biocca, Harms, dan Gregg (2001) dan elemen sense of community dari McMillan dan Chavis (1986). Analisis data menggunakan analisis korelasi Pearson-Product Moment. Hasil analisis Product Moment menunjukkan R = 0,455 dan P = 0,000 (p<0,05). Hasil menunjukkan bahwa social presence memiliki hubungan yang signifikan dengan sense of community sebesar 45,5%. Dengan demikian hipotesis yang diajukan diterima. Kata kunci: Komunitas, Sense of Community, Social Presence. Abstract. The study objective is to determine the relationship between social presence and sense of community among members of art communities at Sriwijaya University. The hypothesis of the study is that social presence has a relationship with the sense of community among members of art community at Sriwijaya University. The research samples were 100 people chosen using quota sampling techniques. The quota for UKM Harmoni research sample was 70 people and Community X was 30 people and the quota of try out sample for UKM Harmoni was as many as 20 people and Community X as many as 10 people. The instruments used were social presence and sense of community scales that refer to the social presence dimensions from Biocca, Harms, and Gregg (2001) and sense of community elements from McMillan and Chavis (1986). Data analysis was using Pearson-Product Moment correlation. The results of the Pearson-Product Moment analysis show r = 0.455 and P = 0,000 (p<0.05). The results show that social presence has a significant relationship with sense of community of 45.5%. Thus the proposed hypothesis is accepted. Keywords: Community, Sense of Community, Social Presence.